A Survey on the Students’ Perceptions in Learning Speaking through Picture Media: Qualitative Method - Adib Ahmada; St Sofia Munawaroh (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The general aims in this research are to find out the students perceptions in learning speaking through picture media at the eleventh grade students of MA Roudlotul Muta’alimin in academic year 2019/2020. Furthermore, the aims can particularly be formulated to know what students perceptions in learning speaking through picture media. This research was categorized as survey research with the descriptive quantitative approach. The subject of this research is the eleventh grade students of MA Roudlotul Muta’alimin in academic year 2019/2020 as the participants totally 18 students. The questionnare was used to collected the data about students perceptions in learning speaking through picture media. And documentation was used to collected a description of the school and respondent. And the result is the eleventh graders of MA Roudlotul Muta’alimin had high integrative motivation to develop English speaking. They also had a high expectation that picture media could help them develop their English speaking skill. They also “strongly agreed” and “agreed” that English speaking mastery will help them to be more confident and courageous in speaking English, express their idea and motivate themselves even reached more than 80%. The response more than 85% of them “strongly agreed” and “agreed” that their mastery of English speaking will able to motivate themself to improve their ability to speak in English and make it easier for them to talk about anything in English by using picture media. In addition, the teacher also has an interesting method in learning English and often to use picture media in learning English.